2018
DOI: 10.22159/ajpcr.2018.v11i11.27557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Characterization of Bioactive Compound of Hamelia Patens Plant With the Gc-MS Spectroscopy

Abstract: Objective: The aim of this study is to evaluate the bioactive compound present in the leaves, root, flower, and stem by gas chromatography (GC) analysis. Novel drugs are isolated from plants against human diseases.Methods: The plant parts (leaves, stem, flower, and root) were collected, washed, shade dried, and powdered, and the methanol extracts of all plant parts were prepared by Soxhlet reflux method. The methanolic extracts were analyzed for the identification of phytochemical compounds present in the Hame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ethanolic leaf extract of Hamelia was obtained using different method of extraction and analyzed by HPLC/ESI-MS method, in which various constituent were observed such as quinic acid, hydroxyl cinnamic acid, catechin, caffeoyl quinic acid, procyanidin B2, epicatechin, ( + )-catechin3-O-glucose, quercetin 3-O-rutinoside, kaempferol-3-O-rutinoside and 3-hydroxyphloretin-2'-O-glucoside [30]. GC-MS analysis showed that Hamelia contains major phytoconstituent which belongs to the different classes of natural products such as Momeinositol, Pentadecanoic acid, 9 octadecenol, Squalene, Gamma-sitosterol, Mitrajavine, Ergost 5-en-3-ol (3,beta), Stigmast-7-en-3-ol [31]. Phytochemicals analysis of Hamelia patens with different extract [32] is given in ▶Tables 2 and ▶3.…”
Section: Phytoconstituentmentioning
confidence: 99%
“…Ethanolic leaf extract of Hamelia was obtained using different method of extraction and analyzed by HPLC/ESI-MS method, in which various constituent were observed such as quinic acid, hydroxyl cinnamic acid, catechin, caffeoyl quinic acid, procyanidin B2, epicatechin, ( + )-catechin3-O-glucose, quercetin 3-O-rutinoside, kaempferol-3-O-rutinoside and 3-hydroxyphloretin-2'-O-glucoside [30]. GC-MS analysis showed that Hamelia contains major phytoconstituent which belongs to the different classes of natural products such as Momeinositol, Pentadecanoic acid, 9 octadecenol, Squalene, Gamma-sitosterol, Mitrajavine, Ergost 5-en-3-ol (3,beta), Stigmast-7-en-3-ol [31]. Phytochemicals analysis of Hamelia patens with different extract [32] is given in ▶Tables 2 and ▶3.…”
Section: Phytoconstituentmentioning
confidence: 99%
“…Medicinal plant in treatment of diseases is as old as man. Many developing countries of the world look upon medicinal plants as possible substitute to synthetic drug because natural sources of herbal medicines are more protective, safe, biodegradable, fewer side effects than artificial and synthetic remedies because the photochemical in the plants extract target the biochemical pathways [1]. The entire dependence of man on plants and plant products directly for his basic needs make plants vital to his survival and the basis of his continued existence.…”
Section: Introductionmentioning
confidence: 99%